ENGLISH LECTURERS’ BELIEFS AND PRACTICES IN TEACHING WRITING THROUGH FEEDBACK - Mubarok, Husni; Shofiyuddin, Muh.; Harsono, Harsono; Sutama, Sutama; Murtiyasa, Budi; Sofiana, Nina; Andriyani, Santi (Universitas Islam Nahdlatul Ulama Jepara, 2024)
Feedback is crucial in the writing learning process, as it enables students to enhance the quality of their work after receiving input from their teacher. Nonetheless, lecturers do not completely grasp the essence of writing education. This study seeks to explore lecturer' beliefs about teaching writing through feedback, describe how these beliefs are applied in teaching practices, and identify any discrepancies between these beliefs and what occurs in the classroom. This research employs a qualitative methodology through a case study. Data were collected via interviews with teachers and students, along with learning observations, and were then analyzed using both qualitative and quantitative methods through descriptive statistics. The findings of the study suggest that feedback plays a vital role in teaching writing, particularly when complemented by Merdeka curriculum centered on outcome-based learning. The different types of feedback used in learning include written feedback, conferencing, and peer feedback. The roles that lecturers take on include facilitator, provider of feedback, and coordinator. The disparity that arises pertains solely to the lecturer's role in providing feedback, without taking any corrective measures. This research suggests that implementing corrective feedback can enhance students' writing skills.